Materialising the king: The royal funeral of King Tāufa`āhau Tupou IV of Tonga - Veys, Fanny Wonu (The Australian journal of anthropology, 2009)
The arrival of the body of King Tāufa‘āhau Tupou IV, in Tonga on 12 September 2006, prompted complex funerary rites modelled on those of the previous monarch, Queen Sālote. Instead of looking at how funerals reinforce kinship ties or what the effective cost is of the objects exchanged, I concentrate on the presented objects, which formed the focal point of the funerary rites. In doing so, I engage with Keane (2005: 184) who asserts the relevance of semiotics in answering the question: ‘How can we both understand things and do full justice to their materiality?’ I argue that traditional prestigious objects (barkcloth, mats, baskets and coconut oil), ‘modern-times’ valuables (flower garlands, flower baskets, and crocheted bed spreads), and contemporary objects (cakes wrapped in cling film, screens with chocolate, plastic baskets filled with bags of crisps, chocolate and sweets), materialise qualities the deceased king embodied as a descendant of a mythical ruler, as the fourth king in the modern Christian dynasty and as a contemporary ruler who reformed both education and economy. A consequence of materialising qualities is that they become contingently bound up with other qualities (Keane 2005: 188). I thus concentrate on those objects where the bundling of qualities is realised visually, examining how barkcloth, fine mats, baskets and coconut oil embody female generative power, protecting, controlling and linking qualities. It is the qualities of the objects bundled in the matter of the objects themselves that make some objects matter more than others.